Pemikiran Ibnu Sina tentang Pendidikan Anak - Rahmat, Jamalludin; Putri, Rizki Yunita; Azhari, Ayu (Zuriah : Jurnal Pendidikan Anak Usia Dini, 2020)
This article discusses Ibn Sina’s thoughts on children’s education. Ibn Sina was a brilliant Islamic thinker who almost mastered all science. Ibn Sina had thoughts on philosophy, medicine, psychology, logic and education. This paper will call on Ibn Sina’s thought about the education of children. Ibn Sina has a large capacity to study children’s education with a variety of sciences. Ibn Sina’s thoughts on the education of children to solve the problems that arise in the midst of Muslims by the base of the Qur’an and Sunnah. Then sense to explore further to explain and strengthen the scientific values that exist in the Qur’an and the Sunnah was used as a guideline. The education of children according to Ibn Sina must pay attention to uniqueness, talents, interests and potential of the child. In addition, it pays attention to aspects of sexual development, reason and child’s soul. In other words, Ibn Sina’s thoughts felt original because of the science of doctors and mental sciences that he had so that the physical and psychic aspects of the child was more concerned in addition to the importance of religious lessons and poetry.Â Ibn Sina did not merely argue (theoretically) but he participated in the educational world because it was once a student and teacher. Some aspects of the educational thinking of Ibn Sina’s children can be applied in Islamic education in Indonesia.